2017
DOI: 10.15191/nwajom.2017.0511
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Decision Support Using VHF Total Lightning Mapping and NLDN Cloud-to-Ground Data in North Alabama

Abstract: (Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This approach is different from other lightning initiation and cessation studies that have either followed a particular storm (e.g., Stano et al 2010) or examined lightning within an area (e.g., MacGorman 16 April 20171417 16 April 2017) 466 1657 (18 April 20172308 18 April 2017) 391 2139 (20 April 20170441 21 April 2017) 422 1928 (22 April 20170120 23 April 2017) 352 0627 (27 April 20171143 (27 April 17 May 20170951 (17 May 2017) 471et al 2011). Schultz et al (2017) demonstrated that an Eulerian approach of examining these data from an end-user standpoint provided extra lead time on the first cloud-to-ground strike. Therefore, this study will use each GLM pixel as a decision point to simulate how decision-support partners would view these data for local area decisions or other areas of interest (e.g., a ball field, stadium, or amphitheater).…”
Section: Glm Stoplight Safety Validationmentioning
confidence: 99%
See 4 more Smart Citations
“…This approach is different from other lightning initiation and cessation studies that have either followed a particular storm (e.g., Stano et al 2010) or examined lightning within an area (e.g., MacGorman 16 April 20171417 16 April 2017) 466 1657 (18 April 20172308 18 April 2017) 391 2139 (20 April 20170441 21 April 2017) 422 1928 (22 April 20170120 23 April 2017) 352 0627 (27 April 20171143 (27 April 17 May 20170951 (17 May 2017) 471et al 2011). Schultz et al (2017) demonstrated that an Eulerian approach of examining these data from an end-user standpoint provided extra lead time on the first cloud-to-ground strike. Therefore, this study will use each GLM pixel as a decision point to simulate how decision-support partners would view these data for local area decisions or other areas of interest (e.g., a ball field, stadium, or amphitheater).…”
Section: Glm Stoplight Safety Validationmentioning
confidence: 99%
“…This increased lead time is due to the spatial information that total lightning measurements from LMA or GLM have versus traditional ground-based networks such as the National Lightning Detection Network (NLDN) or Earth Networks Total Lightning Network (ENTLN). Schultz et al (2017Schultz et al ( , 2018 also found an increase in operational downtime (i.e., work stoppages) using the LMA data versus NLDN observations. Schultz et al (2017Schultz et al ( , 2018 also states that further work is needed to properly assess how the risk assessment changes with spatial-extent observations.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations